Control interno y su relación con la gestión de inventarios en empresas del rubro venta ropa de la ciudad de Iquitos año 2024 - Burgos Torres, Charlotte (2024)
The study focuses on the relationship between internal control and inventory management in clothing retail companies in Iquitos during 2024, highlighting the importance of both elements in enhancing operational efficiency and mitigating risks. The research identifies significant deficiencies in these areas, such as the lack of segregation of duties, inadequate policies, and limited adoption of technology, which result in cost overruns and material losses. Through a quantitative approach and a non-experimental, correlational design, the study demonstrates a positive and significant relationship between internal control and inventory management, where the former plays a crucial role in improving the procedures of the latter. The findings indicate that more than 50% of internal control procedures are implemented in companies in Iquitos, reflecting a moderate level of control. Similarly, inventory management shows a 45% implementation rate, with a more rigorous focus on acquisition processes. Additionally, companies excel in disseminating goals and properly documenting procedures, with 53% and 51% respectively. Regarding inventory management, decision-making on product purchasing and selling is the most prominent feature, reaching 57%. This study underscores that robust internal control is essential for optimizing inventory management, significantly contributing to the success and sustainability of companies in this sector.